A Transient Two-dimensional CFD Evaluation of Indoor Thermal Comfort with an Intermittently-operated Radiant Floor Heating System in an Office Building - Jiying Liu; Xuwei Zhu; Moon Keun Kim; Ping Cui; Shengwei Zhu; Risto Kosonen (International Journal of Architectural Engineering Technology, 2020)
To provide excellent thermal comfort in an energy-efficient manner, the radiant floor cooling and heating system has become an attractive technology. In this work, an intermittently-operated radiant floor heating system combined with a ventilation system for use during the weekdays is proposed via a transient two-dimensional computational fluid dynamics model that takes into account the variation of the indoor heat gain. Additionally, intermittent controls based on the minimum outdoor air temperature and the average water supply and return temperature are proposed. Six specifically-designed outdoor air temperature values ranging from -15oC to 15oC are taken as examples to evaluate the thermal comfort performance using the operative temperature and local thermal discomfort criteria, including the vertical air temperature, floor temperature, and radiant asymmetry. Meanwhile, the percentages dissatisfied induced by the local discomfort parameters above were analyzed.. Results show that for the case with a minimum outdoor air temperature of -14.2 oC, the earlier shut-off of the water supply (e.g., 18:00) cannot contribute to maintaining a comfortable environment at 7:00. To eliminate the effect of the indoor heat gain, a water supply shut-off after 20:00 and the pump starting to recirculate water in the concrete slab at 00:00 are encouraged in the case of an insufficient indoor heat gain during the next daytime. The maximum operative temperature commonly occurred between 4:00-6:00 p.m. A trade-off between the percentages dissatisfied and the operative temperature is finally identified. The control strategy of the shut-off of the water supply for two hours at noon and at least four hours during the nighttime is ultimately obtained to yield the acceptable thermal comfort performance in the intermittent operating mode of a floor heating system while effectively reducing energy consumption.